Potencial terapêutico de um heparinóide isolado do invertebrado marinho Litopenaeus vannamei - Brito, Adriana da Silva (2008)
The occurrence of bioactive compounds in marine organisms comes awaking the interest of the pharmaceutical industry. Heparin, a sulfated polysaccharide which presence was already identified in several marine invertebrates, is very attractive due its remarkable functional versatility. Besides to intervene in blood coagulation, this molecule has a great anti-inflammatory potential. However, its strong anticoagulant activity difficult the clinical exploitation of its anti-inflammatory properties. Thus, the aims of this work were to evaluate the effect of a heparin-like compound (heparinoid), isolated from the cephalotorax of the Litopenaeus vannamei shrimp, on the inflammatory response, hemostasia and synthesis of antithrombotic heparan sulfate by endothelial cells, besides studying some aspects concerning its structure. The purified heparinoid was structurally characterized following an analytical boarding, involving electrophoresis and chromatography. The structural analysis have shown that this compound possess a high content of glucuronic acid residues and disulfated disaccharide units. In contrast to mammalian heparin, the heparinoid was incapable to stimulate the synthesis of heparan sulfate by endothelial cells in the tested concentrations, beyond to show reduced anticoagulant activity and hemorrhagic effect. In a model of acute inflammation, the compound isolated from the shrimp reduced more than 50% of the cellular infiltration. Besides reduce the activity of MMP-9 and proMMP-2 of the peritoneal lavage of inflamed animals, the heparinoid also reduced the activity of MMP-9 secreted by activated human leukocytes. These results demonstrate the potential of heparinoid from L. vannamei to intervene in the inflammatory response. For possessing reduced anticoagulant activity and hemorrhagic effect, this compound can serve as a structural model to direct the development of more specific therapeutical agents to the treatment of inflammatory diseases